A Comparison of the Efficacy of 5 mg Olanzapine and Aprepitant in the Prevention of Multiple-Day Cisplatin Chemotherapy-Induced Nausea and Vomiting. (7th September 2022) - Liu, Guang; Jin, Yilan; Jiang, Ying; Zhao, Juan; Jiang, Caihong; Zhang, Zewei; Zhao, Lanzhen; Li, Hui; Chen, Feng; Wang, Jing; Fan, Hui; Li, Zhenhao; et al.
Abstract : Objective . The significance of this article is to talk about aprepitant and olanzapine 5 mg, compare them, and deeply explore the safety or effectiveness during the whole process of multiple-day cisplatin chemotherapy-induced vomiting and nausea. Methods . This trial was randomized and prospective. It is needed to receive cisplatin chemotherapy (25 mg/m2/d) for three days. Its patients would need to choose to use 5 mg olanzapine or aprepitant for this treatment, combined with 5-HT3 receptor antagonist plus dexamethasone. The primary endpoints were the total protection (TP) during the acute phase (AP) (0–24 hours), delayed phase (DP) (25–120 hours), and overall phase (OP) (0–120 h) between the two groups. The secondary endpoints were the complete response (CR) and total control (TC) during the three phases. The first time of the whole process is particularly important and needs to be observed vigorously. However, the time of the patient's first vomiting symptom is also compared accurately by using the Kaplan–Meier curve. The functional life index vomiting (FLIE) was used to calculate and carefully evaluate the serious impact of nausea and vomiting (CINV) induced by the whole chemotherapy process on the quality of life. About olanzapine, its related symptoms and other side effects and aprepitant were also recorded. Results . (1) The primary endpoint TP rates of the olanzapine and aprepitant groups were similar; for the AP, they were 94.23% (98/104) vs. 95.45% (98/106) P = 0.61 (P = 0.61 ); for the DP, they were 54.81% (57/104) vs. 54.72% (58/106) (P = 0.99 ), and for the OP, the values were 53.79% (58/105) and 55.31% (56/104), respectively (P = 0.99 ). The secondary endpoints, the TC rates, and CR rates were also comparable in the three phases (P > 0.05 ). (2) After research and display, the results showed that there was no significant difference between the two groups when they were used for the first time of vomiting and the FLIE index (P > 0.05 ). (3) The main olanzapine-related adverse event was drowsiness, while that of aprepitant was constipation. Conclusion . The efficacy of 5 mg olanzapine was similar to that of aprepitant, and it also showed an advantageous economic potency ratio in preventing CINV induced by multiple-day cisplatin chemotherapy with increased sedation side effects.